Current and emerging pharmacotherapy for the treatment of childhood acute myeloid leukemia. (22nd November 2022) - Cuglievan, Branko; McCall, David; Robusto, Lindsay; Mireles, M. Estela; Gettys, Suzanne C.
ABSTRACT: Introduction: Pediatric acute myeloid leukemia (AML) is a rare disease that is profoundly heterogeneous at a molecular and clinical level. Although, in recent clinical trials, the 5-year event-free survival rates for childhood AML ranged between 49% and 64%, bone marrow relapse still occurs in up to one-third of cases. New therapies are required to continue progress in this aggressive hematological disease. Optimistically, we anticipate that the next challenge may be not a lack of appropriate therapies but an abundance of potentially effective strategies and a question of how best to incorporate them into pediatric clinical practice. Areas covered: The focus of this review is to highlight all promising agents currently under investigation for pediatric AML, including nucleoside analogs, epigenetic modifiers, targeted small-molecule inhibitors, monoclonal antibodies, novel chemotherapeutics, and immunotherapies. Expert opinion: While AML outcomes have improved over time for pediatric AML patients, our challenge is how to improve outcomes with our new knowledge of genetic and epigenetic aberrations. We posit to incorporate active therapy options into combination strategies and utilize targeted and immunotherapy approaches, as more opportunities are available.